Retinal Microperimetry as a Novel Tool for Early Detection of Subclinical Cognitive Dysfunction and Brain Damage in Type 1 Diabetes: A Pilot Study - Manel Mateu‐Salat; Nicole Stanton‐Yonge; Frederic Sampedro Santaló; José Ignacio Vela; Jesús Díaz Cascajosa; Eva Safont Pérez; Daniela Rego‐Lorca; Ana Chico (Endocrinology, Diabetes & Metabolism)
ABSTRACT Context Retinal microperimetry (MPR) is a non‐invasive method that measures retinal light sensitivity (RS) and gaze fixation stability (GFS). MPR has been described as a marker of cognitive impairment in people with Type 2 diabetes, but it has never been assessed in people with Type 1 diabetes (T1D). Our group described subclinical cognitive alterations, structural brain differences, and increased levels of light chain neurofilament (NfL) in people with T1D and impaired awareness of hypoglycaemia. Objective To measure RS and GFS using MPR in individuals with T1D and evaluate its correlation with neuropsychological assessment, plasma NfL levels and CGM‐derived glucometric parameters. Secondary objectives: to evaluate the possible differences of RS and GFS in people with T1D depending on hypoglycaemia awareness. Design, Setting and Participants Pilot observational study, people with T1D without clinical cognitive impairment, moderate–severe retinopathy or glaucoma. MPR was performed with MAIA3. Results A total of 30 subjects were studied: 40% women, age 58 ± 11 years; T1D duration 31 ± 9 years, mild retinopathy 33%. RS was 27.5 dB (26.1–28.3) and GFS(%) 97.6% (93.5%–99.5%). We found a correlation between RS and memory alteration tests (p = 0.016) and between GFS(%) and a composite of attention and executive neuropsychological tests (p = 0.025). An inverse correlation between GFS and time below range was found. No correlation was found with NfL. Conclusion This first exploratory study in people with T1D supports the potential utility of MPR as a screening tool for subclinical neurocognitive alterations in this population.